Penerimaan Retribusi Dan Pajak Daerah Terhadap Pertumbuhan Ekonomi Melalui Belanja Daerah Sebagai Variabel Intervening - Edy Sugiarto; Sura Klaudia; Munaroh Munaroh (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to determine the relationship between regional taxes and economic growth, regional levies and economic growth, regional taxes and economic growth through regional expenditures as an intervening variable, and regional levies and economic growth through regional expenditures as an intervening variable. The population in this study consisted of the Probolinggo Regency APBD, regional fees, regional gross domestic product at constant prices, and local tax reports. The Probolinggo Regency APBD in one decade (2012-2021) consisted of 40 samples from all variables, namely all regional tax reports, regional levies, regional gross domestic product, and the samples in this study. I obtained secondary data from the Central Bureau of Statistics (BPS) of Probolinggo Regency. The analysis technique uses SPSS 25, and the test results show that regional taxes have an effect on economic growth, regional levies do not, regional taxes moderated by regional spending have an effect, and regional levies moderated by regional expenditures have an effect on economic growth. Keywords: Regional Tax, Regional Retribution, Regional Expenditure, Economic Growth.